PERANCANGAN COWORKING SPACE DI KOTA SINGKAWANG - Abdurrahman Jalil, Ahmad Fauzan; Gultom, Bontor Jumaylinda; Nurhamsyah, Muhammad (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Singkawang City has the potential to increase the service sector in the creative industry in the film sector which is influenced by the potential of Singkawang City tourist destinations. The workers in the creative industry sector, not only come from within the city but also from outside the city, both for work and family trips while working. To meet the needs of facilities and workspace, Coworking Space was chosen. The design method starts with site selection based on the RTRW in trade and service areas, easy access and adequate infrastructure. At the analysis stage, referring to the actors, types of activities and facilities for the creative film industry, analysis of location, circulation, orientation, vegetation, and zoning. The area is divided into four areas, namely the parking area, reception area, green open space (RTH) area and work area. The design concept is a parking area that is divided into car parking and motorbike parking. The reception area is a receptionist area and the hall is a barrier from the public area in the parking lot. The green open space area is a large park to be used as a place for film production, promotions, and the like, as well as reducing noise entering the work area. The work area as a coworking space is designed with a hierarchy on each floor. The ground floor is semi-public, the first and second floors are semi-private, the third floor is private, and the rooftop is semi-public.